Funções de produção das culturas de milho e feijão através de estudo experimental e simulado - Parizi, Ana Rita Costenaro (2010)
The development of math models can available a tool to estimate and understand the behavior of the system in face of diferent situations, helping in the decision-making process, through a simplified representation of reality, allowing to simulate several scenes and to estimate the different action courses impact about the production systems, helping in the activity planning. In the case of use simulation models of crops production, about different irrigation strategies, the procedure allows to get all the possible informations, that in field experiments would require time and necessary features to the research. So, this work proposes a simulation of maize and beans crops production, considering a field experiment characteristics and the agricultural year climate characteristics, in which the experiment was managed, with the goal to calibrate, test and apply a simulation model to the cycle of maize and beans crops in the region of Santiago, RS. As experimental results, it was obtained variations in maize and beans crops growth, development, and production, with the apply of different irrigation strategies. The irrigation blades growth increased the grain and dry matter production of the studied crops. The production model applied could simulate properly the grain and dry matter production for both crops. The different strategies of irrigation simulated by the model, influenced the water balance components and in the final productivity of studied crops. Water blades of 800 mm e 500 mm resulted in maize and beans production decrease, respectively. The efficiency of water application from 550 mm and 500 mm to the maize and the beans have been decreased, respectively. The proposed model can be used as a tool for regional planning in the deployment of maize and beans crops in irrigated conditions and allows the identification of irrigation strategies that result in higher grain production, and could be considered an excellent tool for predicting crops yields in irrigated conditions. Thus, it was possible to offer to the studied region, yield data with the irrigation use and, especially, with the simulation use, providing greater security for producers and technicians of the region, in future installations of irrigated systems.